Comparisons of predictive values of sarcopenia with different muscle mass indices in Korean rural older adults: a longitudinal analysis of the Aging Study of PyeongChang Rural Area - Jang IY (Dove Medical Press, 2018)
Il-Young Jang,1,2,* Hee-Won Jung,3,4,* Chang Ki Lee,5 Sang Soo Yu,2 Young Soo Lee,1 Eunju Lee1 1Department of Internal Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, 2PyeongChang Health Center & County Hospital, Gangwon-Do, 3Graduate School of Medical Science and Engineering, Korea Advanced Institute of Science and Technology (KAIST), Daejeon, 4Geriatric Center, Seoul National University Bundang Hospital, Gyeonggi-Do, 5Goldman Urology Clinic, Seoul, Republic of Korea *These authors contributed equally to this work Purpose: It is important to define lean muscle mass when diagnosing sarcopenia, but there is still controversy on the clinical implication of sarcopenia derived by height, weight, and body mass index (BMI) adjusted muscle mass indices. We aimed to evaluate the longitudinal clinical relevance of 3 sarcopenia definitions in the Korean population. Patients and methods: We conducted comprehensive geriatric assessments for 1,379 community-dwelling older participants in the Aging Study of PyeongChang Rural Area (ASPRA) cohort and followed them up prospectively for death, institutionalization, and disability every 3 months. Sarcopenia was defined using the Asian Working Group consensus algorithm, combining grip strength, gait speed, and muscle mass.Results: Among 1,343 participants (mean age: 76 years, 741 women) analyzed, there were 29 deaths and 89 institutionalizations during 22.0 ± 8.3 months follow-up (mean ± SD). All three muscle indices correlated to age and sex. All sarcopenia criteria with muscle mass indices of height, weight, and body mass index (BMI) adjustment significantly predicted death or institutionalization. However, when adjusted for age and sex, only the sarcopenia criteria with muscle mass index of height adjustment were significantly associated with major adverse health outcomes.Conclusion: Adjusting age and gender, the sarcopenia definition from the quintile-based muscle index of height adjustment could predict death or institutionalization in Korean community-dwelling older adults. Keywords: cohort studies, frailty, geriatric assessment, muscle index, muscle mass, muscles, sarcopenia